2023
DOI: 10.3390/ijms24021472
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Adipose-Derived Stem Cells in Diabetic Foot Ulcer Treatment: Clinical Effectiveness, Safety, Survival in the Wound Site, and Proteomic Impact

Abstract: Although encouraging results of adipose-derived stem cell (ADSC) use in wound healing are available, the mechanism of action has been studied mainly in vitro and in animals. This work aimed to examine the safety and efficacy of allogenic ADSCs in human diabetic foot ulcer treatment, in combination with the analyses of the wound. Equal groups of 23 participants each received fibrin gel with ADSCs or fibrin gel alone. The clinical effects were assessed at four time points: days 7, 14, 21 and 49. Material collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Hence, the presence of ADSCs might enable the orchestration of wound healing, accelerating physiologic healing, and, hence, preventing the vicious cycle of ongoing inflammation. This potential mechanism of action appears relevant for the treatment of chronic diabetic ulcers where ulcers treated with ADSC-fibrin gels resulted in a greater and faster reduction in wound size and achieved complete healing in a significantly higher number of patients [35]. Notably, Forcheron et al found an increased influx of lymphocytes in ADSC-grafted minipigs with radiation-induced fibrosis, with significantly improved wound healing [36].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the presence of ADSCs might enable the orchestration of wound healing, accelerating physiologic healing, and, hence, preventing the vicious cycle of ongoing inflammation. This potential mechanism of action appears relevant for the treatment of chronic diabetic ulcers where ulcers treated with ADSC-fibrin gels resulted in a greater and faster reduction in wound size and achieved complete healing in a significantly higher number of patients [35]. Notably, Forcheron et al found an increased influx of lymphocytes in ADSC-grafted minipigs with radiation-induced fibrosis, with significantly improved wound healing [36].…”
Section: Discussionmentioning
confidence: 99%
“…Human adipose-derived stromal cells (ADSCs) were obtained according to established protocol as previously described [67] and cultured on the piezoelectric PVDF scaffolds electrospun with different collector rotational speeds (200, 1000, and 2000 rpm). First, PVDF samples were cut and sterilized by radiation.…”
Section: In Vitro Testsmentioning
confidence: 99%
“…In turn, two phase III trials assessed the safety and effectiveness of a fibrin glue loaded with PRP, which formed a protective barrier against the external environment and fostered re-epithelialization [ 148 , 149 ], and Granexin ® , a hydroxyethyl cellulose gel for the loading of aCT1, which is a synthetic peptide known to stimulate re-epithelialization and consequent wound closure [ 150 , 151 ]. A phase III trial evaluated the potential of an allogeneic ADSC-loaded fibrin gel that possesses anti-inflammatory and pro-angiogenic effects and can stimulate granulation tissue formation [ 152 , 153 ]. In addition, many pilot trials have emerged as small-scale preliminary studies to evaluate the feasibility and assist the planning and modification of larger-scale studies for the efficacy assessment of wound dressings such as PRP Concepts Fibrin Bio-Matrix, a fibrin-based matrix enriched with platelets [ 154 ]; Piscean-derived collagen dressing with hemostatic effects [ 155 ]; Omeza, a fish-derived collagen matrix that maintains a moist healing environment to promote wound healing [ 156 ]; Helaquis Matrix, a HA matrix that facilitates cell migration and proliferation and maintains wound moisture [ 157 ]; and Meso Wound Matrix™, which is another collagen matrix but derived from porcine peritoneum membrane [ 158 , 159 ].…”
Section: Biomaterial-based Wound Dressings In the Clinical Settingmentioning
confidence: 99%